2006
DOI: 10.3171/jns.2006.104.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuronal and glial apoptosis in the adult facial nucleus after intracranial nerve transection

Abstract: These findings may ultimately lead to new therapeutic strategies in patients suffering from facial nerve palsy due to an intracranial lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…With respect to signals driving the stress-induced secondary hyper-ramification, we have again confirmed that chronic stress, using the repeated restraint paradigm, does not induce any measurable alterations in proteins associated with inflammation or neurodegeneration (Mattsson et al 2006;Graeber et al 2011). This finding, rather than being surprising, is consistent with observations that microglial de-ramification is associated with an increased level of inflammatory signaling within the brain (Wynne et al 2009;Kettenmann et al 2011).…”
Section: Summary and Future Directionssupporting
confidence: 87%
“…With respect to signals driving the stress-induced secondary hyper-ramification, we have again confirmed that chronic stress, using the repeated restraint paradigm, does not induce any measurable alterations in proteins associated with inflammation or neurodegeneration (Mattsson et al 2006;Graeber et al 2011). This finding, rather than being surprising, is consistent with observations that microglial de-ramification is associated with an increased level of inflammatory signaling within the brain (Wynne et al 2009;Kettenmann et al 2011).…”
Section: Summary and Future Directionssupporting
confidence: 87%
“…Our preliminary studies showed that facial motor neurons could be adequately stained by the application of 1 -4% FG after 48 h survival time, as suggested by other literature. 18,22,24,25 Injection of FG into the main trunk of the facial nerve, including injections distal to the anastomosis site can, therefore, enable the numbers of motor neurons that project their axons through the anastomosis site to be obtained. Additionally, intrathecal FG injection did not affect facial nerve function, hence the results from the present study confirmed the reliability of the FG retrograde labelling method.…”
Section: Facial Nerve Injury and Regeneration In Ratsmentioning
confidence: 99%
“…Moreover, PACAP deficiency in PACAP knock-out mice leads to a significant delay of axonal regeneration of axotomized facial nerve confirming the role of PACAP in axonal regeneration process (Armstrong et al, 2008). On the other hand, it is possible to speculate that PAC1R downregulation after nerve axotomy may correlate to increased apoptotic death of MNs of facial motor nucleus (Mattsson et al, 2006).…”
Section: Pacap and Alsmentioning
confidence: 58%